2003
DOI: 10.3168/jds.s0022-0302(03)73754-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Amounts and Degradability of Dietary Protein on Lactation, Nitrogen Utilization, and Excretion in Early Lactation Holstein Cows

Abstract: Five treatment diets varying in crude protein (CP) and rumen undegradable protein (RUP) were calculated to supply a postruminal lysine to methionine ratio of about 3:1. Diets were fed as a total mixed ration to 65 Holstein cows that were either primiparous (n = 28) or multiparous (n = 37) from 21 to 120 d in milk to determine effects on lactation and nitrogen utilization. Crude protein % and calculated RUP (% of CP) of diets [on a dry matter (DM) basis] were: 1) 19.4, 40 (HPMU), 2) 16.5, 34 (LPLU), 3) 16.8, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
69
2
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(105 citation statements)
references
References 20 publications
27
69
2
7
Order By: Relevance
“…The MUN values were significantly affected by dietary treatments (P < 0.01), with the lowest values in cows fed diet A, followed by diets B and C, and the highest in cows fed diet D. The MUN values increased with CP levels. The observation was consistent with some studies (Davidson et al, 2003;Groff and Wu, 2005;Promkot and Wanapat, 2005), while Flis and Wattiaux (2005) found that a 1% change in the dietary protein level did not cause a significant change in the MUN content.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The MUN values were significantly affected by dietary treatments (P < 0.01), with the lowest values in cows fed diet A, followed by diets B and C, and the highest in cows fed diet D. The MUN values increased with CP levels. The observation was consistent with some studies (Davidson et al, 2003;Groff and Wu, 2005;Promkot and Wanapat, 2005), while Flis and Wattiaux (2005) found that a 1% change in the dietary protein level did not cause a significant change in the MUN content.…”
Section: Resultssupporting
confidence: 92%
“…Milk composition was not affected by increasing CP levels. The lack of responses in milk production and milk composition was consistent with others' observations that these did not change when dietary protein varied from 16.7 to 18.4% (Davidson et al, 2003), from 16.4 to 20.4% (Mulligan et al, 2004), from 16.4 to 18.0% (Wattiaux and Karg, 2004), and from 14.6 to 18.3% (Castillo et al, 2001). While some researchers observed significant differences in milk yield or composition with dietary protein from 13.1 to 17.0% (Frank and Swesson, 2002), it has been reported that milk production benefits from > 15% protein, but increasing the protein above 17% has no further effect (Groff and Wu, 2005), and dietary protein has only a low effect on milk fat and protein concentration (Sutton, 1989).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Plasma urea-N has repeatedly been shown to correlate positively to the level of dietary CP (Marini and Van Amburgh, 2003), RDP (Davidson et al, 2003), or OEB (Fiems et al, 1999a). Johnson and Preston (1995) found that increasing the CP level from 10 to 16% in steer diets by 2% steps caused a 1-to 3-mg increase in PUN concentrations between each CP level.…”
Section: Discussionmentioning
confidence: 99%
“…Os primeiros 14 dias foram usados para adaptação das vacas às dietas experimentais e as coletas de dados efetuadas nos 7 dias posteriores. As vacas foram agrupadas de acordo com a produção inicial de leite (30 kg/dia), média de 160 dias de lactação, escore corporal três e meio (Edmonson et al, 1989) e na 4 a ordem de lactação, distribuída em três quadrados latinos simultâneos, cada um com quatro animais, submetidos a quatro dietas em quatro períodos.…”
Section: Methodsunclassified